Drinking water quality assessment of Ergene River Basin (Turkey) by water quality index: essential and toxic elements - Tokatli, Cem (Penerbit Universiti Kebangsaan Malaysia, 2019)
Ergene River Basin is the most significant aquatic habitat for Thrace Region and also one of the most polluted watersheds in Turkey. The objectives of this study were to determine some essential-toxic element accumulations in drinking water of settlement areas located in Ergene River Basin and evaluated the water quality in terms of local public health. Drinking water samples were collected from 30 stations in dry (summer) season of 2018. Cluster Analysis (CA) was used to classify the investigated elements and villages and Weighted Arithmetic Water Quality Index (WAWQI) was used to assess the water quality. According to results of elemental CA, 11 statistically significant clusters were formed in terms of elemental densities and according to results of locational CA, 3 statistically significant clusters were formed in terms of drinking water qualities. According to results of WAWQI, the risk sequence of the elements in drinking water of the system as follows: Se > As > Mo > B > Ba > Cr > Pb > Mn > Ni > Cd > Cu. Although Ergene River Basin is known as a very contaminated freshwater ecosystem, it was determined that the groundwater of the basin has I. - II class water quality, in general. Selenium accumulations detected in almost all the investigated villages exceeded the drinking water limit of 10 ppb. Arsenic, boron and molybdenum accumulations detected in some villages exceeded the drinking water standards. Although concentrations of some elements in some locations were exceed the limit values and recorded as quite high levels, the majority of investigated element concentrations in drinking water of the basin have been found to be in the range of human consumption standards.